Barium aluminate improved iron ore for the chemical looping combustion of syngas. (15th August 2020) - Wang, Haiming; Dou, Xiaomin; Veksha, Andrei; Liu, Wen; Giannis, Apostolos; Ge, Liya; Thye Lim, Teik; Lisak, Grzegorz
Highlights: Chemical looping combustion was applied for the treatment of MSW syngas. BaAl2 O4 greatly improved the reactivity of iron ore as the oxygen carrier. Lattice oxygen activity was enhanced due to the increased oxygen vacancies. Interaction between BaAl2 O4 and iron ore gave rise to highly porous morphology. Abstract: Chemical looping combustion (CLC), as an advanced combustion technology, has attracted much attention because of its applicability to a variety of fuels and its ability to achieve inherent carbon capture. However, CLC of municipal solid waste (MSW) has been seldom reported. In this study, we investigated the CLC of simulated MSW-derived syngas using iron ore (IO)-based oxygen carriers (OCs). To enhance the redox activity of the IO, barium aluminate (BaAl2 O4 ) was used for the first time as a promoter of the OC. It was found that the surface decoration with BaAl2 O4 significantly improved the redox performance of IO over the temperature range of 700–900 °C. Almost 100% syngas combustion over 30 redox cycles was achieved by IO modified with 10% of BaAl2 O4 (IO-10BA) at a space velocity of 31700 h −1, whereas only 70% combustion efficiency was achieved by pristine IO. Additionally, BaAl2 O4 doping improved the oxygen transport capacity of the IO by 36.2%. Based on complementary characterization analyses, we found that more oxygen vacancies were formed in the modified OC due to the oxygen non-stoichiometry nature of the BaAl2 O4 and its interaction with the iron oxide species. This interaction facilitated the rapid migration of the lattice oxygen in the bulk phase, thereby enhancing the reactivity and increasing the oxygen transport capacity of the OCs. The addition of BaAl2 O4 also induced a change to the solid morphology, making the OC become more porous over redox cycles, a phenomenon that was partly responsible for the high combustion performance of the IO-10BA.